Spring-summer drought induces extremely low radial growth reactions in North-Tyrrhenian Pinus pinea L. - Piraino, Sergio (2020)
Climate projections predict shifts in environmental conditions, with cascade effects on forest growth dynamics. As such, Pinus pinea L., an ecologically important low-elevation Mediterranean tree, can be threatened by drought events. The occurrence of negative stem growth anomalies ("negative pointer years", or NPY) and its relation to climatic conditions were analyzed, as well as the influence of extreme dry spells upon the species growth. NPY were temporally independent among the analyzed forest stands, likely due to local factors. We observed that NPY depended on dry and hot conditions during the spring-summer period at both sites, while differences in the NPYclimate reflected the species medium term dendroclimatological signal. Extremely dry years directly reduced stem growth rates. Water stress differentially affected growth at each site, likely reflecting local adaptation to droughts. Because of the increasing drought trend expected for the Mediterranean basin, our findings must be considered regarding the conservation and management of these forests.